PENGARUH KOMISARIS INDEPENDEN, LEVERAGE, PROFITABILITAS, DAN TIPE AUDITOR TERHADAP PENGUNGKAPAN INTELLECTUAL CAPITAL (Perusahaan Food And Beverage Yang Terdaftar Di Bursa Efek Indonesia Tahun 2012-2016) - Arista Irfan Prakoso, 13.05.52.0106; Suwarti, Titiek (Students Journal of Accounting and Banking, 2017)
The era of globalization has changed the business strategy of a business based on labor to a knowledge-based business. Intellectual capital becomes an important factor for companies in improving competitiveness. This study aims to analyze the influence of independent commissioners, leverage, profitability, and type of auditors to the disclosure of Intellectual capital.Â The population of this study are all food and beverage companies listed in Indonesia Stock Exchange 2012-2016. The sample was chosen using purposive sampling method and obtained 48 samples of food and beverage companies. Sources of data obtained through the website of BEI, the website of each company, and ICMD. Analysis method used in this research is multiple linear regression analysis.Â The results of this study indicate that the independent commissioner have significant influence on intellectual capital disclosure, leverage has no significant effect on intellectual capital disclosure. profitability has no significant effect on intellectual capital disclosure, and auditor type has a significant effect on intellectual capital disclosure.Keywords:Â Intellectual Capital Disclosure, Independent Commissioner, Leverage, Profitability, and Type of Auditors